Trade Integration, FDI, and Productivity - Javorcik, Beata; Iacovone, Leonardo; Fitrani, Fitria (World Bank, Jakarta, 2015)
Policy attitude towards trade integration and foreign direct investment (FDI) is often a controversial yet popular subject. This note presents evidences from recent policy researches that arguing that engaging in an open trade and investment regime have brought productivity gains which is key factor for sustaining increase in income per-capita. Evidence from Indonesia also suggests that foreign owned plants have become increasingly important, generating a significant share of exports and overall output, as well as more productive and more export intensive than domestic plants, and to spend more on RD and training. FDI also have positive impact on firms in the same sector, through competition and demonstration effects, and in upstream sectors, as suppliers to foreign-owned plants improve the quality of their own products to meet their clients more exacting needs. Evidence also suggests a positive impact from import competition in improving allocative efficiency across manufacturing plants which is a key element in driving productivity in manufacturing sector.